Anatomical Variations in Palmar Creases and Their Correlation to The Intelligence Capacity of Libyan Medical and Dental Students of Omar Al-Mukhtar University. - Abdullatif H. Annaas; Osama Othman Mohammed Ambarak; Abeer Amer; Haneen A. Akilah; Ayah H. Salim; Hala A. Ibrahim; Muhammad A.M Abdul Rahman (International Journal of Medical Research and Review, 2023)
Background: For centuries, clinicians, anthropologists, and palmists have found the creases in the palm interesting. However, only in the last fifty years that research's started to examine the variations in these creases. Based on the three main palmar creases, thenar, proximal, and distal transverse creases, four patterns of palmar creases are identified; nonvariant, Sydney, Suwon, and simian. Previous studies of palmar creases revealed that familial components, race, sex, and age are factors that influence the expression of palmar crease patterns. Simian patterns of palmar creases are linked to various congenital diseases, some characterized by low level of intelligence.Aim: This paper aims to investigate the variations in palmar crease patterns among medical and dental students of Omar Al-Mukhtar University and to study the range of intelligence capacity associated with each pattern.Materials and methods: The study was conducted on 183 students. A paper-based IQ test was performed and photos were taken from both palms of all participants.Results: Out of 183 participants, the nonvariant pattern of palmar creases was found in 92%, in which, 100 students have bilateral 2 points of origin palmar creases and 48 students have bilateral 3 points of origin palmar creases, whereas 18 participants have one palm of 2 points and the other palm of 3 points of origin. Unilateral simian was the dominant type in the aberrant palmar creases, followed by bilateral Sydney, then unilateral Sydney, and Suwon.Conclusion: The students with unilateral simian have the highest average score of 47.166 followed by bilateral nonvariant and unilateral nonvariant. Students with unilateral Sydney have the lowest average score of 41.